2013
DOI: 10.1074/jbc.m112.423723
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Suppression Increases PH Domain and Leucine-rich Repeat Phosphatase (Phlpp)1 Expression in Chondrocytes to Suppress Akt Signaling and Matrix Secretion

Abstract: Background: Hdac3 depletion in osteo/chondroprogenitor cells causes severe osteopenia and decreases long bone length. Results: Akt and mTOR activities were reduced and Phlpp1 levels were increased in Hdac3 deficient chondrocytes. Conclusion: Hdac3 deletion suppresses the Akt/mTOR pathway by increasing expression of the protein phosphatase Phlpp1. Significance: Hdac3 and Phlpp1 have crucial roles in regulating chondrocyte hypertrophy and cartilage regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 54 publications
(19 reference statements)
5
76
2
Order By: Relevance
“…This fact is particularly interesting taking into account the fact that mTOR signaling can be activated by IGF-1 signaling and is active during growth plate development also has been shown to regulate cell size. 35 IGF-2 is the other ligand that can bind to the IGF1R. This paternal imprinted gene has been shown to have a role in skeletal development.…”
Section: Igf-1 and Chondrocytesmentioning
confidence: 99%
“…This fact is particularly interesting taking into account the fact that mTOR signaling can be activated by IGF-1 signaling and is active during growth plate development also has been shown to regulate cell size. 35 IGF-2 is the other ligand that can bind to the IGF1R. This paternal imprinted gene has been shown to have a role in skeletal development.…”
Section: Igf-1 and Chondrocytesmentioning
confidence: 99%
“…We previously demonstrated that Hdac3 also suppresses chondrocyte hypertrophy (3). Deletion of Hdac3 in osteo/ chondroprogenitor cells and committed osteoblasts reduces bone mass (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting cell suspension was placed into micromasses consisting of 2 ϫ 10 5 cells in a 10 l drop of DMEM. After 1 h, chondrogenic medium (DMEM, supplemented with 5% FBS, 1% antimycotic/antibiotic and 1ϫ mixture of insulin, transferrin, and selenium (ITS) (Invitrogen, Carlsbad, CA)) was added to the cultures for the indicated periods of time (3,25,26). Cells were infected with adenoviral (Ad)-GFP or Ad-Cre (MOI ϭ 10) on day 0 and harvested for analysis on day 3.…”
Section: Generation Of Hdac7mentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility proclaims that PHLPP directly modifies histones on these specific promoters (Reyes et al 2014) Moreover, HDAC inhibitors regulate the expression of PHLPP1. A study demonstrated that HDAC3 upon association with PHLPP1 promoter region controls chondrocyte hypertrophy and matrix content by activating AKT through repressing PHLPP1 expression (Bradley et al 2013). During chondriogenesis, stimulation with TGFβ, a potent activator of chondrogenesis, causes HDAC3 association with the PHLPP1 promoter leading to decreased transcription of PHLPP1.…”
Section: Post-translational Modifications By Phlpp Regulate the Epigementioning
confidence: 99%